2020
DOI: 10.1039/d0tb01370f
|View full text |Cite
|
Sign up to set email alerts
|

Injectable polypeptide-engineered hydrogel depot for amplifying the anti-tumor immune effect induced by chemo-photothermal therapy

Abstract: The immunosuppressive tumor microenvironment has caused great obstacles to tumor immunotherapy, especially less tumor-associated antigens released from tumor sites. Herein, Ag2S QD/DOX/Bestatin@PC10ARGD genetically engineered polypeptide hydrogel PC10ARGD as sustained-release material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The change in temperature can control the gel-sol transformation of thermosensitive hydrogels and release active factors for enhanced therapy [ 35 ]. Pedersen et al reported that a polyvinyl alcohol/gold nanorod (AuNR) hydrogel was heated to <50 °C under NIR irradiation and liquefied in 15–20 s, and the pulsed release model cargo of fluorescein isothiocyanate controlled by NIR irradiation was realized successfully [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The change in temperature can control the gel-sol transformation of thermosensitive hydrogels and release active factors for enhanced therapy [ 35 ]. Pedersen et al reported that a polyvinyl alcohol/gold nanorod (AuNR) hydrogel was heated to <50 °C under NIR irradiation and liquefied in 15–20 s, and the pulsed release model cargo of fluorescein isothiocyanate controlled by NIR irradiation was realized successfully [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the physical properties, such as viscosities of hydrogel aqueous solutions, swelling abilities, and mechanical properties after shaping, can be altered to some extent [ 100 , 116 ]. Furthermore, these multifunctional features of hydrogels also provide excellent opportunities for manipulating these hydrogels on various engineering techniques, including 3D printing, microfluidic spinning, and co-coaxial extrusion technology [ [159] , [160] , [161] ].…”
Section: Hydrogels As the Artificial Microenvironmentmentioning
confidence: 99%
“…An impressive spectrum of cell biology, versatile hydrogels, and clinical pathology has enabled the formation of 3D tissue analogs with promoted vascularization. To date, an extensive study has demonstrated various organ types that can be mimicked by hydrogels, including but not limited to bone [ 77 , 95 , [163] , [164] , [165] ], kidney [ [52] , [53] , [54] ], liver [ [55] , [56] , [57] ], lung [ 160 , 166 , 167 ], muscle [ [58] , [59] , [60] , [61] ], and brain [ 138 , 168 ]. Ultimately, the generation of these reproducible and accurate 3D organoids has extended the downstream translational applications, including tissue regeneration ( Table 3 ), organ-on-chips ( Table 4 ), and drug screening ( Table 5 ).…”
Section: Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hou et al used genetically engineered polypeptide hydrogel PC10ARGD as a sustained-release system that delivered Bestatin which is an immune adjuvant for mammary carcinoma treatment. The hydrogel serves as a drug delivery depot for sustained drug release of Bestatin, which further inhibits tumour metastases and microvessel formation but amplified T lymphocytes function ( Hou et al, 2020 ). Liu et al developed a smart hydrogel based on alginate, which hybridized with immunoadjuvant CpG oligonucleotide and conjugated with an adenosine triphosphate (ATP)-specific aptamer.…”
Section: Applications Of Hydrogels As Delivery Systems For Cancer Immunotherapymentioning
confidence: 99%